Synthesis, molecular docking and tyrosinase inhibitory activity of the decorated methoxy sulfonamide chalcones : in vitro inhibitory effects and the possible binding mode - Thawanrat Kobkeatthawin; Suchada Chantrapromma; Thitipone Suwunwong; Lydia Rhyman; Choong, Yee Siew; Ponnadurai Ramasami (Penerbit Universiti Kebangsaan Malaysia, 2021)
In this study, a series of sulfonamide chalcones derivatives was synthesized and its chemical structures were confirmed by spectral characteristics. The synthesized compounds were evaluated for their tyrosinase inhibitory activities along with molecular docking study. The tyrosinase inhibitory results indicated that compounds 5b, 5c, 5f, 5g and 5h displayed the significant tyrosinase inhibitory activity and comparable to the standard drug (kojic acid). Compound 5c exhibits the most potent tyrosinase inhibition among the synthesized compounds with IC50 = 0.43±0.07 mM, L-DOPA as the substrate, and better than that of the standard kojic acid (IC50 = 0.60±0.20 mM). Molecular docking studies showed that the binding mode of some compounds is in the tyrosinase binding pocket surrounding the copper in the active site. The correlation between the docking results with IC50 values showed that the binding mode prediction of the test compounds would also be convincing. This comprehensive study allows for a possible mechanism for the antityrosinase activity of the sulfonamide chalcones. These sulfonamide chalcones bind to copper atoms of tyrosinase which responsible for the catalytic activity of tyrosinase. These compounds may be used as a lead for rational drug designing for the multi-functional tyrosinase inhibitor.